Peran Japan Foundation Dalam Diplomasi Kebudayaan Jepang Di Indonesia Tahun 2011-2013 - Kholisuddin (2014)
The diplomacy of japanese culture try to reattract the international interest into their country. in indonesia, the diplomacy of japaneese culture was promoted to change the Indonesian thought about Japaneese which colonized over this country many years ago. in additian, Japan also hopes that there will no more malari which broke the japan - indonesian relationship. threfore, the organization of japan foundation was established 5 years after the malari in 1974 to reduce indonesian's hastred for japan in order to make the cooperation between both country can be run well. this writing will explain what kind of role that japan foundation establish to be a stabilisation of the diplomacy relationship between japan and indonesia in increasing the cooperation between this two countries and also to change the way of indonesian think about japan. in addition, japan foundation become a connector between both of japanese and indonesian culture. Kata Kunci: Diplomasi Kebudayaan, Japan Foundation, Budaya, Kerjasama, Organisasi Internasional PENDAHULUAN